Monster house - Buscemi, Steve, 1958-; Gyllenhaal, Maggie, 1977-; Kenan, Gil,; Lee, Jason, 1970-; Schrab, Rob,; Starkey, Steve, (Sony Pictures Entertainment, 2006)
Tres adolescentes descubren que la casa vecina esta realmente viva, respira, y es un temible monstruo.